Influencia del ruido y cobertura vegetal de los espacios verdes urbanos sobre la diversidad de aves en la ciudad de Loja - Martín Medina, José Alexander (2023)
Worldwide, urbanization impacts biodiversity, causing animals and plants to adapt, disappear, or be exposed to new conditions. This research evaluated the effect of noise and vegetation cover on bird diversity in urban green spaces. This was done in the southern area of the city of Loja. Point counts were used to study birds in 7 green spaces; noise (dBA) and vegetation cover (richness, abundance, basal area, canopy density and tree height) were measured. Generalized linear mixed models (GLMm) with Poisson distribution adjustment were performed to analyze the relationships between variables and identify the one with the most significant effect on bird species richness and abundance. As for the results, 333 birds were recorded, where the most abundant species were Zenaida auriculata (65), Furnarius cinnamomeus (42) and Columba livia (41). The highest number of richness was in the Reinaldo Espinosa Botanical Garden (14 species), while abundance was higher in Parque Central, representing 21% of birds recorded. The urban green spaces with the highest noise levels were Parque los Molinos (68.77-75.43 dBA) and Parque Simón Bolívar (69.67-78.20 dBA). Noise and vegetation cover did not influence the richness and abundance of urban birds, even though canopy density and tree species richness were the most significant predictors of bird diversity. Consequently, the study concludes that birds adapt to the urban environment, which makes the number of species more homogeneous among the different areas, with between 11 and 14 bird species recorded in the study, although this range of diversity could decrease in the future. Keywords: bird diversity, urban green spaces, generalized linear model, noise, urbanization.